Enhancing thermal conductivity of epoxy composites via f‐BN@f‐MgO hybrid fillers assisted by hot pressing - Wu, Xudong; Yu, Haojie; Wang, Li; Meng, Xingguang; Huang, Zhikun; Liu, Xiaowei; Gong, Xiaodan; Liu, Jinyi (Polymer composites, 2023)
High thermal conductive polymeric composites are extremely desired for the thermal management of electronic devices due to the rapid development of the modern microelectronic industry. Herein, the functionalized boron nitride (BN) and magnesium oxide (MgO) hybrid fillers (f‐BN@f‐MgO) were synthesized and used to prepare the enhanced thermal conductive epoxy (EP) composites through the hot‐pressing method. The results demonstrated that the covalent binding of BN and MgO in the hybrid fillers reduced the interface thermal resistance effectively between fillers and matrix and the hot‐pressing induced force facilitated the construction of the continuous thermal conduction paths. Consequently, the as‐prepared epoxy composite at 40 wt% hybrid fillers loading had high thermal conductivity (TC) (1.97 W/[m·K]), outstanding insulating performance (6.9 × 1015 Ω cm) and excellent thermal stability. Furthermore, a probable thermal conduction mechanism was proposed to illustrate the high TC of the epoxy composite. Therefore, this study provides a new approach to preparing epoxy composites with outstanding performances.